Analysis of KOICA under Gender Mainstreaming Approach: A Case Study in Darkhan, Mongolia - Chica-Morales, Patricia; Domenech del Río, Antonio J. (Routledge, 2024)
This chapter aims to analyse how the Korean government has advanced its gender mainstreaming (GM) policy within its assistance programmes, despite facing challenges in promoting gender equality within its institutional framework. Specifically, it delves into the case of the Korea International Cooperation Agency (KOICA) and its application of GM principles, while also discussing potential enhancements for KOICA’s gender approach in accordance with global standards. This chapter focuses particularly on the study case of the KOICA’s Green Ger Village Master Plan in Darkhan, Mongolia. This case study contributes to assessing the application of GM principles across all KOICA projects as a pervasive concern rather than solely within initiatives targeted to women.
Keywords: Discriminación sexual - Corea del Sur; Políticas de género; Enfoque de género; Desarrollo; Corea del Sur